Prevalence, determinants, and outcomes of SARS‐COV‐2 infection among cancer patients. A population‐based study in northern Italy. (22nd September 2021) - Serraino, Diego; Zucchetto, Antonella; Dal Maso, Luigino; Del Zotto, Stefania; Taboga, Francesca; Clagnan, Elena; Fratino, Lucia; Tosolini, Francesca; Burba, Ivana
Abstract: Background: It is well established that cancer patients infected with SARS‐CoV‐2 are at particularly elevated risk of adverse outcomes, but the comparison of SARS‐CoV‐2 infection risk between cancer patients and cancer‐free individuals has been poorly investigated on a population‐basis. Methods: A population‐based study was thus conducted in Friuli Venezia Giulia region, northeastern Italy, to estimate prevalence and determinants of SARS‐CoV‐2 infection among cancer patients, as compared to cancer‐free individuals, and to evaluate adverse outcomes of SARS‐CoV‐2 infection. The study included 263, 042 individuals tested for SARS‐CoV‐2 in February–December 2020 with cancer history retrieved through the regional cancer registry. Odds ratios (ORs) of SARS‐CoV‐2 positivity, with corresponding 95% confidence intervals (CIs), were calculated using multivariable logistic regression models, adjusted for sex and age. Hazard ratios (HRs) adjusted for sex and age for intensive care unit (ICU) admission and all‐cause death were estimated using Cox models. Results: Among 26, 394 cancer patients tested for SARS‐CoV‐2, the prevalence of infection was 11.7% versus 16.2% among 236, 648 cancer‐free individuals, with a corresponding OR = 0.59 (95% CI: 0.57–0.62). The prevalence was much higher (29% in both groups) during the second pandemic wave (October–December 2020). Among cancer patients, age ≥80 years and cancer diagnosis ≥13 months before SARS‐CoV‐2 testing were the major risk factors of infection. Among 3098 infected cancer patients, the fatality rate was 17.4% versus 15.8% among 23, 296 negative ones (HR = 1.63, 95% CI: 1.49–1.78), and versus 5.0% among 38, 268 infected cancer‐free individuals (HR = 1.23, 95% CI: 1.12–1.36). No significant differences emerged when considering ICU admission risk. Conclusion: Albeit cancer patients reported reduced SARS‐CoV‐2 infection risk, those infected showed higher mortality than uninfected ones and infected cancer‐free population. Study findings claim for continuing to protect cancer patients from SARS‐CoV‐2, without reducing the level of oncologic care. Abstract : SARS‐CoV‐2 infection risk among cancer patients as compared to cancer‐free individuals has been poorly investigated on a population‐basis. This population‐based study found 40% lower odd of SARS‐CoV‐2 positivity among tested cancer patients than cancer‐free individuals. Nonetheless, SARS‐CoV‐2‐positive cancer patients reported higher risk of death, both as compared to negative ones or to positive cancer‐free population. Study findings claim for continuing to protect cancer patients from SARS‐CoV‐2 infection, without reducing the level of oncologic care.